Proces izgorevanja pri članih negovalnega tima v patronažnem varstvu - Kaučič, Boris Miha (Obzornik zdravstvene nege, 2002)
Continuous negative stress causes the burn out syndrome. The article presents basic features of the burn out syndrome. The aim of the research study was to determine the burden in a part of the community nursing team in Adolf Drolc Health Centre.
Keywords: Burnout, professional; Delovne naloge; Home care services; Izgorevanje poklicno; Nursing, team; Patronažna služba; poklicni stres; sindrom izgorevanja; Workload; zdravstvena nega; Zdravstvena nega, tim